A geochemical study of the formation of hydrocarbons in structures (South –Al Rusafeh-1, Zamleh-1,Dbessan-2) at the northeastern end of the Palmyra folding zone-Syria - إبراهيم أحلام; خرستين نبيه; فضة زينة (Latakia University Journal -Basic Sciences Series, 2023)
This research presents a geochemical study of the organic matter present within the rock structures in three wells to the south of AL-Rusafeh 1 well, Dbessan 2 and Zamleh 1. The ROCK EVAL device was used to determine the degree of maturity of the organic matter and the maturity of the parent rocks and their ability to generate hydrocarbon and to determine the type of hydrocarbon whether it was migratory or locally generated, and a chromatograph was used to extract Bitumen and determine the value of hydrogen charcoal capable of producing. The geochemical study was conducted for a group of samples belonging, by studying the rocky crumbs of 21 samples from the Kurachina Dolomite and Alamanos Shale formations. Liquid hydrocarbons, but with acceptable to medium capabilities in general, did not enter the stage of gas generation except in a primary or marginal way, and that the gas discovered in these compositions is gas migrating from deeper levels than that of the upper Paleozoic rocks.